Accelerated atherosclerosis in SLE: mechanisms and prevention approaches - Wilhelm, Ashley J. (2012)
Systemic lupus erythematosus (SLE) is a multi-organ autoimmune disease characterized by increased serum autoantibody levels and tissue damage. With improved diagnosis and more effective treatment of the resultant kidney disease, accelerated atherosclerosis has become a major cause of morbidity in patients suffering from SLE. Although the exact mechanisms for SLE-accelerated atherosclerosis are unknown, multiple factors have been established as potential players in this process. Among these potential players are dysregulation of T and B cell populations and increased circulating levels of inflammatory cytokines. In addition, SLE patients exhibit a proatherogenic lipid profile characterized by low HDL and high LDL and triglycerides. Recent therapeutic approaches have focused on targeting B cells, the producers of autoantibodies, but most studies do not consider the effects of these treatments on atherosclerosis. Evidence suggests that T cells play a major role in SLE-accelerated atherosclerosis. Therefore, therapies targeted at T cells may also prove invaluable in treating SLE and atherosclerosis.